Transformasi Masyarakat Wih Pesam Menuju Desa Digital Bebas Stunting - Septima S, Richasanty; Hajimi, Hajimi; Karmila, Karmila; Novellia, Gracia; Putri, Juwita; Wulandari, Miranti; Pitriani, Pitriani; Zikri, Agustia; Maharami, Ilham; Husairi, Ahmad; Ariga, Irwan; Riski, Rahmad; Putri, Wenny Julia; Bahgie, Mutuah; Fitranuddin, Fitranuddin; Akmal, Maulana; Rapiah, Rapiah; Umar, Umar; Syahputra, Safrika (Jurnal Pengabdian Pada Masyarakat Indonesia, 2023)
In the current era technology is experiencing rapid development. Global technological advances have influenced all aspects of life, including economics, health, arts, public services and education. Digital technology is an information technology that prioritizes activities carried out by computer or digital rather than using human power. With the development of digital technology, many fields have benefited from its development. With this technology, village communities should also be able to experience ease in accessing technology because nowadays villages are encouraged to progress and be independent, with the hope of being able to develop the various potentials they have for the advancement of village development, but of course in some villages it is possible not to utilize this digital technology because that community service creates programs that introduce modernizing digital technology. The methods used are discussion and practice. Increasing understanding of village officials and the community means increasing digital literacy skills and showing that the objectives of the White Elephant University 2023 Thematic real work course are quite achievable and successful.